Numerical Simulation of the Influence of Gear Modification on the Meshing Stiffness - Wang Zhiqin; Wang Xiaosun; Wang Shiru; Wu Shijing (Jixie chuandong)
In order to explore the influence of gear modification on the meshing stiffness，two different methods are used to calculate the gear meshing stiffness.First，the gear is parametrically modeled by Pro/E secondary development，and the gear model is imported into Abaqus software for finite element simulation calculation.The time-varying mesh stiffness curve is obtained through data processing.Second is based on the energy method of the analytical method to calculate the time-varying mesh stiffness curve.The results show that within a certain range，the coincidence degree of gear meshing decreases with the increase of gear displacement coefficient and the average meshing stiffness of the gear decreases as the gear displacement coefficient increases.